Clonally expanded cytotoxic CD4+ T cells and the pathogenesis of IgG4-related disease - Hamid Mattoo; John H. Stone; Shiv Pillai (Taylor & Francis Group, 2017)
IgG4-related disease (IgG4-RD) is a systemic condition of unknown cause characterized by highly fibrotic lesions, with dense lymphoplasmacytic infiltrates containing a preponderance of IgG4-expressing plasma cells. CD4+ T cells and B cells constitute the major inflammatory cell populations in IgG4-RD lesions. IgG4-RD patients with active, untreated disease show a marked expansion of plasmablasts in the circulation. Although the therapeutic depletion of B cells suggests a role for these cells in the disease, a direct role for B cells or IgG4 in the pathogenesis of IgG4-RD is yet to be demonstrated. Among the CD4+ T-cell subsets, Th2 cells were initially thought to contribute to IgG4-RD pathogenesis, but many previous studies were confounded by the concomitant history of allergic diseases in the patients studied and the failure to use multi-color staining to definitively identify T-cell subsets in tissue samples. More recently, using an unbiased approach to characterize CD4+ T-cell subsets in patients with IgG4-RD - based on their clonal expansion and ability to infiltrate affected tissue sites - CD4+ CTLs have been identified as the major CD4+ T-cell subset in disease lesions as well as in the circulation. CD4+ CTLs in affected tissues secrete pro-fibrotic cytokines including IL-1β, TGF-β1, and IFN-γ as well as cytolytic molecules such as perforin and granzymes A and B. In this review, we examine possible mechanisms by which activated B cells and plasmablasts may collaborate with the expanded CD4+ CTLs in driving the fibrotic pathology of the disease and describe the lacunae in the field and in our understanding of IgG4-RD pathogenesis.